Threshold Concepts in Neuroscience: Identification Challenges, Educational Opportunities and Recommendations for Practice - Sandrone, Stefano; Alavian, Kambiz N. (Frontiers in Education, 2021)
Threshold concepts are recent, yet already established, aspects of medical education. However, they represent a new area in neuroscience education, especially given the recency of neuroscience as a field of research in its own right when compared to more established STEM disciplines. In this article, we reviewed the existing literature on threshold concepts in clinical/translational neuroscience education and argued the relevance and the importance of biomarker as a new threshold concept. Moreover, we included a set of recommendations for practice that has the potential to improve the students’ experience by offering them an authentic journey and, ultimately, to build a community of practice with shared goals and an enhanced diversity, with beneficial effects at several societal levels.